Porous carbon-based robust, durable, and flexible electrochemical device for K+ detection in sweat. Issue 6 (18th February 2022) - Jiang, Tingting; Yin, Bing; Liu, Xiaobo; Yang, Lihui; Pang, Hongyu; Song, Jie; Wu, Shuo
Abstract : A highly robust, durable, and flexible ion sensor was prepared by coating polymer membranes on porous carbon electrodes. The ion sensor realized the real-time analysis of human sweat. Abstract : Ion sensors are attracting attention for real-time ion monitoring in biological fluids, which requires the development of sensitive, stable, flexible, robust and durable ion-selective electrodes (ISEs) and reference electrodes (REs). In this paper, a highly robust and durable ion sensor was prepared by coating polymer membranes on porous carbon electrodes. A high sensitivity of 58.6 mV per decade with a rapid response time of 0.8 s, and a negligible potential drift less than 1.4 mV h −1 were obtained simultaneously. In addition, after six washing cycles, the K + ion sensors still have an average sensitivity of 53.2 mV per decade. Importantly, the polymer membrane permeated and packed the porous structure tightly, and thus the ion sensors presented outstanding robustness and durability. The Nernst slope of the K + ion response fluctuated from 60.2 to 57.9 mV per decade between 0° and 60° bending angles. Repeated bending for 8000 cycles did not result in the delamination of the sensing and reference membranes or reduction of the sensitivity (57.4 mV per decade). Furthermore, five kinds of flexible reference electrodes (LEC, bare Ag, bare Ag/AgCl, PVB + NaCl on Ag/AgCl, PVC/agarose + NaCl on Ag/AgCl) were fabricated and evaluated in terms of the sensitivity for Cl − and long-term stability. Finally, the flexible K + ion sensor was integrated with microfluidic channels and connected to a portable electrochemical workstation to realize the real-time analysis of human sweat.